Performance indicators to be explored in order to win Premier League matches (Research, Society and Development, 2023)
Football is a dynamic collective sport that involves the actions of players on the field, in addition to the availability and application of player data. Being a sport extensively investigated in terms of performance analysis, there is still a need for more predictive analyzes to better understand the indicators of success. Due to these aspects, this research aimed to verify the influence of the market value of football clubs, as well as the influence of the venue and the tactical/technical aspects - shots on target, corners, crosses, ball possession and passes -, to win Premier League matches. To carry out this research, data from all 380 matches of the PL 2015/2016 season were used. The Transfermarkt website was used to collect the market value of the teams and the Daily Mail website to collect the matches data. Data analysis was performed using the Weka software. The results showed that the market value and the venue, separately, were not relevant to the victories, but when associated to tactical/technical indicators, both contributed with the victories of the teams. Concept A teams, with higher market values, achieved more victories than the concept C teams, with lower market values, in the home games when the aforementioned associations were analyzed. The results of the performed analyzes show that direct and indirect game actions are relevant for teams to win matches played at home, especially for the ones with higher market value.